Correlation between the material constitution components in apatite-nepheline ores of the Khybiny Rock Massif (the Kola Peninsula) - Marchevskaya, V. V.; Korneeva, U. V. (2020)
Raw apatite-nepheline ores of the Khibiny alkaline massif are similar in terms of the set of ore-forming minerals and differ in their quantitative ratio. A special place among apatite-nepheline ores is occupied by ores of tectonically destroyed zones, which are widespread in the Khibiny apatite-nepheline deposits. Destruction zone ores are product of secondary changes in raw ores and are characterized by the presence of finely dispersed secondary minerals represented by hydrated micas, zeolites and clay minerals. In the aquatic environment they form colloidal sediments with active surface properties. This fact, as well as thin films of clay and other minerals formed on the surface of apatite grains, cause a decrease in the degree of hydrophobicity of fluorapatite and deterioration of the selectivity of apatite flotation. According to the analytical determinations of the chemical components of the ores and their mineralogical composition, a correlation-regression analysis of the ratio of the components of the material composition of the ores has been performed. The results of correlation-regression analysis have shown that the presence of hypergenically changed ores related to difficult-to-treat ones can be identified by lower ratios of sodium and potassium oxides, as well as sodium and aluminum relative to their average. The presence of products of nepheline change in all ores processed has allowed revealing the most stable correlation between nepheline and sodium oxide, rather than aluminum oxides, in contrast to the earlier opinion. The very high correlation relationship between fluorapatite, nepheline, and titanite and the oxides of phosphorus, sodium, and titanium, respectively, and the statistical significance of the correlation and regression coefficients allow determining the content of these minerals using the regression equations presented in the paper. Рядовые апатит-нефелиновые руды месторождений Хибинского щелочного массива близки по набору рудообразующих минералов и отличаются их количественным ...